Incremental Growth of Mid- to Upper-Crustal Magma Bodies During Arabia–Eurasia Convergence and Collision: A Petrological Study of the Calc-Alkaline to Shoshonitic Meghri–Ordubad Pluton (Southern Armenia and Nakhitchevan, Lesser Caucasus). (25th May 2018) - Rezeau, Hervé; Leuthold, Julien; Tayan, Rodrik; Hovakimyan, Samvel; Ulianov, Alexey; Kouzmanov, Kalin; Moritz, Robert
ABSTRACT: The composite Meghri–Ordubad pluton (MOP) is located in the southernmost Lesser Caucasus and crops out over ∼1000 km 2 in southern Armenia and Nakhitchevan. It is characterized by nested intrusions incrementally emplaced over ∼30 Myr from the Middle Eocene to Early Miocene, coeval with the closure of the Neotethyan Ocean and the regional Arabia-Eurasia continental collision. We recognize three compositionally distinct intrusive series in the MOP: a medium- to high-K calc-alkaline series 1 dominated by gabbro, quartz diorite and tonalite, a shoshonitic to high-K calc-alkaline series 2 including gabbro, monzogabbro, monzodiorite, monzonite and syenite, and a high-K calc-alkaline adakitic series 3 characterized by the emplacement of lamprophyre dikes followed by porphyritic granodioritic intrusions and dikes. Amphibole thermobarometry together with detailed petrography, mineral chemistry and experimental mineral stability P–T diagrams indicate a polybaric crystallization history and magma emplacement at mid- to upper crustal levels (0·1–0·3 GPa). Mineral textures and compositions reveal open-system magmatic processes such as mafic magma replenishment and reactivation of crystal mushes prior to transport towards shallower crustal levels in the MOP. The evolution of magma chemistry (calc-alkaline vs shoshonitic) and mineral assemblages (amphibole-bearing vs amphibole-free) indicate fluctuation in primary melt alkali and water contents over time. Such chemical evolution is ascribed to a decrease in the degree of partial melting of a chemically heterogeneous, but isotopically homogeneous, mantle source. Overall, the MOP is characterized by the successive emplacement of hydrous magma batches in the mid- to upper crust and petrological processes that were dominated by fractional crystallization (± crustal assimilation) upon cooling and, or, decompression (± degassing). We propose a new temporal and spatial petrogenetic model for the MOP, encompassing three long-lived, chemically distinct magmatic series incrementally assembled over 30 Myr within a pre-, syn- and post-collisional geodynamic setting.